KEKERASAN DALAM RUMAH TANGGA: ANALISIS YURIDIS, DINAMIKA REGULASI, DAN PERLINDUNGAN KORBAN DI INDONESIA - Mujito, Mujito; Sopyan , Aziz Wardhana; Darmawan , Didit; Yuristiawan , Agung; Suwito, Suwito (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Domestic violence remains a major challenge in the administration of law and the fulfillment of human rights in Indonesia. This phenomenon is triggered by various factors, including the ignorance of the perpetrator, justification of old social norms, and weak legal awareness in the community. Law No. 23/2004 on the Elimination of Domestic Violence comes as a major milestone to strengthen victim protection, by emphasizing prohibited forms of violence and providing a number of special rights for victims. However, implementation in the field is often ineffective due to cultural barriers, weak law enforcement, and constraints in regulatory harmonization. This research highlights the importance of state commitment in strengthening legal protection, as well as the need for education and comprehensive strategies at various levels of society. Thus, efforts to eliminate domestic violence must be an ongoing agenda, involving the collaboration of all elements of society and responsive and inclusive legal reforms.